Characteristics of The Drainage Network of the Abu Ghar Basin :A Hydrological Study - Assistant Professor Dr. Adnan Odeh Flaih, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The studies dealing with drainage water characteristics of the basins dry studies that gained wide attention from geographers in general and hydrologists in particular , they contain indicators and characteristics reflect the reality of geological and climate , as well as the human factor , and the basin area of research is the Wadi Abu Gar , which is located between the brackets length- ̅ 48( ) ˚ 45and ) ˚ 46 -¯ 28( to the east, and latitudes ) 28 - ¯ 54( and ) ˚ 30- ̅ 37( north , and bordered on the north low Alsalibat , hand south drilling sub From the east, the Wadi al -Athir basin ,and from the west, Wadi Khanka and the Sudair basin